The determination of optimal cells disintegration method of Candida albicans and Candida tropicalis fungals - M. V. Rybalkyn (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
Candidiasis is common infectious disease that affects the mucous membranes, skin, nails, hair, and internal organs. Now Ukraine has neither domestic nor registered imported vaccine against candidiasis. The development of vaccine for prevention and treatment of candidiasis is a key issue in modern medicine and pharmacy. Similar research is actively conducted in many countries of the world: Russia, USA, Japan and others. It should be noted that researchers have not yet reached a consensus view which vaccine is most effective with candidiasis. There are several types of vaccines: live, inactivated, subunit and others. In this article, we consider getting the potential subunit vaccine from Candida albicans and Candida tropicalis fungi. Subunit vaccine is composed of fragments of antigens that can provide an adequate immune response. These vaccines can be represented by particles of microbes. It is known that the main substances in cells of genus Candida fungi, which have antigenic properties, are proteins and polysaccharides. However, the question of their localization in the layers of the cell wall and cytoplasm nowadays require more detailed studies. Many researchers to highlight cytoplasm antigens and all the other layers of the cell use the following methods: grinding cells with quartz sand, destroying them in different machine disintegrating, freezing and thawing a multi others. To obtain potential subunit vaccine fungi were rejected by methods that are based on the processing of biomass fungi chemicals (extraction, hydrolysis). The aim of this work was to study experimentally the destruction method of Candida albicans and Candida tropicalis fungi.